UPAYA MENINGKATKAN MOTORIK KASAR ANAK MELALUI KEGIATAN SENAM CERIA KELOMPOK B2 - Sri Rawanti; Wahyuni Ulpi; Hasnika Hasnika; Endah Setiyowati; Nur Luthfi Ardhian (CERED Indonesia, 2022)
his study aimed to improve rough motoric skills through cheerful gymnastics in group B2 at Lestari Kindergarten, Palopo City. The problem at Lestari Kindergarten in Palopo City was that children's rough motoric skills have not developed well. The method used in this research was classroom action research (CAR) with 14 children. Data collection techniques used were observation and documentation. Data analysis techniques used in this study were quantitative analysis techniques and qualitative data analysis techniques. The results of the study on increasing rough motoric skills through cheerful gymnastics in group B2 at Lestari Kindergarten show that the pre-cycle was 52%, the first cycle was 55.7, and at the second cycle developed very well 79.7%.